2022
DOI: 10.1063/5.0123685
|View full text |Cite
|
Sign up to set email alerts
|

Directional control of absorptivity with quasi-localized guided modes

Abstract: We present a guided mode resonance grating that exhibits high-Q resonances with highly selective directional absorption around 3.7  μm. The grating is designed to create slow guided mode resonances with near-flat dispersion relation. Weakly coupled resonators enable such resonances with small dispersion characteristics. We study the dynamic control of directional absorption using the design presented. We show that weaker dispersion of resonance frequency allows a strong sensitivity concerning the directionalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…For Ti 2 CO 2 , the absorption maxima at 3.2 eV energy was reported in [45] with an absorption coefficient of 3.6 × 10 5 . In another research [23], in case of oxygen and fluorine adsorbed V 3 C 2 , absorption coefficient of 3.8 × 10 5 and 3.3 × 10 5 is reported in the visible region, respectively. In the present study, the observed absorption coefficient for O, S, Se and Te adsorbed V 2 N MXene in the visible region is 1.75 × 10 5 , 3.48 × 10 5 , 3.80 × 10 5 and 4.20 × 10 5 , respectively (see table 2), which is higher than the previously reported studies.…”
Section: Optical Propertiesmentioning
confidence: 87%
See 1 more Smart Citation
“…For Ti 2 CO 2 , the absorption maxima at 3.2 eV energy was reported in [45] with an absorption coefficient of 3.6 × 10 5 . In another research [23], in case of oxygen and fluorine adsorbed V 3 C 2 , absorption coefficient of 3.8 × 10 5 and 3.3 × 10 5 is reported in the visible region, respectively. In the present study, the observed absorption coefficient for O, S, Se and Te adsorbed V 2 N MXene in the visible region is 1.75 × 10 5 , 3.48 × 10 5 , 3.80 × 10 5 and 4.20 × 10 5 , respectively (see table 2), which is higher than the previously reported studies.…”
Section: Optical Propertiesmentioning
confidence: 87%
“…New 2D transition metal carbides and nitrides called 'MXenes' have shown promise in several areas, including ion batteries [12][13][14][15], electromagnetic interference shielding [16][17][18], conductive thin films [19,20], photonics [21][22][23][24], and photothermal therapy [25,26]. The reason for their popularity in such applications is their metallic composition, broad range of optical absorption and tunable surface chemistry.…”
Section: Introductionmentioning
confidence: 99%